Validation of the ECOS-16 Questionnaire in Koreans with Osteoporosis - Jung Sub Lee (Asian Spine Journal, 2016)
Study DesignProspective study.PurposeTo evaluate the reliability and validity of the adapted Korean version of the Quality of Life Questionnaire of the European Foundation for Osteoporosis (ECOS-16).Overview of LiteratureThe validity of the Korean version of ECOS-16 has not been completely demonstrated.MethodsTranslation/retranslation of the English version of ECOS-16, and full cross-cultural adaptation were performed. The Korean version of a visual analog scale measure of pain, and the Korean versions of ECOS-16 and of the previously validated short form-36 (SF-36) were mailed to 158 consecutive patients with osteoporosis. Factor analysis and reliability assessment using kappa statistics of agreement for each item, intraclass correlation coefficient, and Cronbach's α were done. Construct validity was evaluated by comparing responses to ECOS-16 with responses to SF-36 using Pearson's correlation coefficient.ResultsFactor analysis extracted three factors. All items had a kappa statistics of agreement >0.6. The ECOS-16 showed good test/re-test reliability (0.8469) and internal consistency of Cronbach's α (0.897). The Korean version of ECOS-16 showed significant correlation with SF-36 total scores and with single SF-36 domains scores.ConclusionsThe adapted Korean version of the ECOS-16 was successfully translated and showed acceptable measurement properties. It is considered suitable for outcome assessments in Korean patients with osteoporosis.